The transition from school to work: Analysis of the supply of and demand for labour among youth without higher education in urban areas - Lavado, Pablo (2014)
The study examines the job market of «urban youth» aged between 18 and 35 without higher education (university or technical) based on household surveys (Encuesta Nacional de Hogares – Enaho) and specialized surveys (Encuesta Nacional de Habilidades – Enhab; Encuesta de Transición de la Escuela al Trabajo – Entrans). The results show, firstly, supply constraints in the period 2007- 2012, which coincides with the massification of higher education over the last ten years. Secondly, it was found that students from public schools are more liable to complete high school with maxi- mum educational attainment. Thirdly, it was estimated that urban youths aged 15 to 29 cited in the Entrans 2012—and who received job training in the year prior to the survey—are 4.1 times more likely to obtain «adequate employment» in terms of pay, adequate contracts, and health insurance. Finally, a case is made for strengthening technical and specialized skills taught at school.